Light-directed 5′→3′ synthesis of complex oligonucleotide microarrays - Albert, Thomas J. (Oxford University Press, 2003)
Light-directed synthesis of high-density microarrays is currently performed in the 3′→5′ direction due to constraints in existing synthesis chemistry. This results in the probes being unavailable for many common types of enzymatic modification. Arrays that are synthesized in the 5′→3′ direction could be utilized to perform parallel genotyping and resequencing directly on the array surface, dramatically increasing the throughput and reducing the cost relative to existing techniques. In this report we demonstrate the use of photoprotected phosphoramidite monomers for light-directed array synthesis in the 5′→3′ direction, using maskless array synthesis technology. These arrays have a dynamic range of >2.5 orders of magnitude, sensitivity below 1 pM and a coefficient of variance of <10% across the array surface. Arrays containing >150 000 probe sequences were hybridized to labeled mouse cRNA producing highly concordant data (average R(2) = 0.998). We have also shown that the 3′ ends of array probes are available for sequence-specific primer extension and ligation reactions.